2015
DOI: 10.1007/s13277-014-2934-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA double-strand break repair gene XRCC7 genotypes were associated with hepatocellular carcinoma risk in Taiwanese males and alcohol drinkers

Abstract: Hepatocellular carcinoma (HCC) is the fifth most common cancer worldwide, the prevalence and mortality rates of which are very high in Taiwan. The study aimed at evaluating the contribution of XRCC7 G6721T, together with cigarette smoking and alcohol drinking lifestyles, to the risk of HCC. In this hospital-based case-control study, the association of XRCC7 single nucleotide polymorphism G6721T with HCC risk was examined by polymerase chain reaction (PCR)-restriction fragment length polymorphism (RFLP) among 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…Very recently, similar to our present finding, it is reported that polymorphisms of the XRCC4 and XRCC5 might be risk factors for gastric cancer development especially among persons with positive FH [25]. Also it has been reported that XRCC7 G6721T polymorphism had no effect on hepatocellular carcinoma risk to the whole population, but had a protective effect on HCC risk among males and alcohol drinkers [17].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Very recently, similar to our present finding, it is reported that polymorphisms of the XRCC4 and XRCC5 might be risk factors for gastric cancer development especially among persons with positive FH [25]. Also it has been reported that XRCC7 G6721T polymorphism had no effect on hepatocellular carcinoma risk to the whole population, but had a protective effect on HCC risk among males and alcohol drinkers [17].…”
Section: Resultssupporting
confidence: 90%
“…Although NHEJ is the major pathway for DSB repair in human cells and acts during all phases of the cell cycle [1], only a few studies have been reported on the association between G6721T polymorphism of the XRCC7 gene and risk of multifactorial traits including, several types of cancers. However the results were not consistent [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 80%
“…Recently, others and our team have reported that specific genotypes may be combined with cigarette smoking habits and contribute to increased HCC risk, such as the polymorphisms on CYP1A1 (41), N-acetyltransferase 2 (42) and tumor necrosis factor-alpha (9). Several genomic markers did not have joint effects with cigarette smoking habit on HCC risk (5,8). However, the overall mechanisms are very complex and need more investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, it interacts with the Ku70/ Ku80 heterodimer protein in the nonhomologous end joining (NHEJ) repair and recombination [86][87][88]. More than 200 of GSNPs have been reported in the XRCC7 gene, some of which are reported to afect tumorigenesis of malignant tumors [89][90][91][92][93]. In Guangxi area, several reports imply XRCC7 rs7003908 polymorphism (T to G) may be associated with HCC related to AFB1 exposure [49,94].…”
Section: The Xrcc7 Gsnps and Afb1-hcc Among Guangxiese Populationmentioning
confidence: 99%